2017
DOI: 10.1063/1.4982708
|View full text |Cite
|
Sign up to set email alerts
|

A study of tantalum pentoxide Ta2O5 structures up to 28 GPa

Abstract: Tantalum pentoxide Ta 2 O 5 with the orthorhombic L-Ta 2 O 5 structure has been experimentally studied under high pressure using synchrotron angle-dispersive powder

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
3
3
1
Order By: Relevance
“…Our observed powder XRD patterns closely match observations from previous studies on bulk Ta 2 O 5 [17,18,55] and Ta 2 O 5 thin films [39,56]. Figure 1 compares an integrated pattern collected at ambient conditions with calculated profiles of the proposed Ta 2 O 5 phases.…”
Section: Methodssupporting
confidence: 86%
See 4 more Smart Citations
“…Our observed powder XRD patterns closely match observations from previous studies on bulk Ta 2 O 5 [17,18,55] and Ta 2 O 5 thin films [39,56]. Figure 1 compares an integrated pattern collected at ambient conditions with calculated profiles of the proposed Ta 2 O 5 phases.…”
Section: Methodssupporting
confidence: 86%
“…While none of the plausible phases provide an obviously superior match to experimental data, visual inspection suggests that L SR reproduces the observed XRD features (figure 1), especially low intensity ones, slightly better than the other structures. Indeed, Stavrou et al [18] observed XRD patterns almost identical to ours and concluded that L SR was the correct structure based on this correspondence. However, our Rietveld refinements do not quantitatively support this interpretation.…”
Section: Discriminating Between Plausible Structuressupporting
confidence: 83%
See 3 more Smart Citations